Effect of potassium bubbles on the thermal shock fatigue behavior of large-volume potassium-doped tungsten alloy. (1st December 2022) - Ma, Xiaolei; Feng, Fan; Zhang, Xiaoxin; Wang, Ting; Liu, Xiang; Lv, Wei; Lang, Shaoting; Ge, Changchun; Yan, Qingzhi
Abstract: A newly developed large-volume potassium-doped tungsten (W–K) plate with a thickness of 15 mm and a weight of 25 kg by powder metallurgy plus hot rolling was prepared to meet the requirements of the International Thermonuclear Experimental Reactor (ITER) in engineering application. In order to clarify the effect of K doping on the thermal shock performance of W–K alloy, transient thermal shock tests with a single-pulse duration of 1 ms for 100 shots at room temperature were performed. The absorbed power density is set to 0.33, 0.44, 0.55 and 0.66 GW m −2, respectively. Furthermore, the microstructure, Vickers micro-hardness before and after the transient thermal shock, thermal conductivity and relative density were also characterized. The results indicate that the cracking threshold of rolled W–K is 0.44–0.55 GW m −2, which possesses a better transient thermal shock resistance compared with the most of advanced W-based materials. This is mainly because K doping can significantly improve the high-temperature stability and mechanical properties of W material without reducing its thermal conductivity. In particular, K bubbles can also effectively inhibit the formation and propagation of cracks during thermal shock. Moreover, the cracking mechanism of rolled W–K alloy is also discussed in detail. This study is helpful for building a trusted ITER database on advanced W-based materials that provides useful references for the selection of future plasma-facing materials.